2018
DOI: 10.21077/ijf.2018.65.4.62647-11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different feed ingredients on digestive enzymes activity and on the histology of liver and intestine in Labeo rohita Hamilton, 1822

Abstract: Present study compared the effect of fishmeal and selected plant-origin feed ingredients on digestive enzymes activity as well as on the histology of liver and intestine in abeo rohita. Guar meal (GM), soybean meal (SBM), cotton seed meal (CSM) and canola meal (CM) were used as experimental feed ingredients in the four treatment diets, while fishmeal (FM) incorporated diet served as control. There were three replicates for each of the treatment and control diets. The experiment was conducted in 15 fiber glass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The study found a significant reduction in growth performance of the fish at higher salinity, 15 ppt group. In freshwater fish, it is proven that higher saline conditions negatively affects its growth and similar results were reported in Clarias batrachus (Sahoo et al 2003) Heterobranchus longifilis (Fashina-Bombata and Busari, 2003) and Nile tilapia (Iqbal et al, 2012). Freshwater fish need to spend more energy at higher salinity to maintain an osmotic balance between the body fluid and external environment leading to reduced growth (Boeuf and Payan, 2001).…”
Section: Resultsmentioning
confidence: 62%
“…The study found a significant reduction in growth performance of the fish at higher salinity, 15 ppt group. In freshwater fish, it is proven that higher saline conditions negatively affects its growth and similar results were reported in Clarias batrachus (Sahoo et al 2003) Heterobranchus longifilis (Fashina-Bombata and Busari, 2003) and Nile tilapia (Iqbal et al, 2012). Freshwater fish need to spend more energy at higher salinity to maintain an osmotic balance between the body fluid and external environment leading to reduced growth (Boeuf and Payan, 2001).…”
Section: Resultsmentioning
confidence: 62%
“…Likewise, Kuzmina (1996) [15] explained the feeding behavior and biochemical composition of feed could affect the digestive enzyme activity. Khalid and his co-worker (2018) [25] recorded maximum amylase activity in Labeo rohita fed with canola meal while maximum protease activity was recorded in fish fed with cotton seed meal. He also explained that rohu, Labeo rohita fed with guar meal diets showed maximum lipase activity in the whole intestine.…”
Section: Resultsmentioning
confidence: 99%
“…Intestine of fish comprises mucosa, submucosa, muscularis and serosa layers (Mokhtar et al, 2015). According to Ozel et al (2018), mucosal layer is composed of epithelium, lamina propria and muscularis mucosa (Mumford et al, 2007) and could be influenced by biotic and abiotic factors (Khojasteh, 2012) such as species and diet (Raskovic et al, 2011;Iqbal et al, 2018), feeding pattern, body shape and age (Cao et al, 2011). Intestinal Fig.…”
Section: Resultsmentioning
confidence: 99%